2002
DOI: 10.1254/jjp.90.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatostatin on Rabbit Isolated Coronary Arteries

Abstract: ABSTRACT-Somatostatin analogues are capable of inhibiting vascular smooth muscle and endothelial cell proliferation. However, little is known about the effect of somatostatin on vascular responses in endothelium-denuded coronary arteries in vitro. The aim of this work was to determine whether or not somatostatin prevented the contractile response induced by 5-hydroxytryptamine and acetylcholine in endothelium-denuded rabbit coronary arteries. Somatostatin attenuated the contraction produced by 5-hydroxytryptam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Somatostatin‐induced relaxation of smooth muscle has been observed in the gastrointestinal system and in blood vessels [5–7]. However, it has also been reported that somatostatin can induce contraction of smooth muscle [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin‐induced relaxation of smooth muscle has been observed in the gastrointestinal system and in blood vessels [5–7]. However, it has also been reported that somatostatin can induce contraction of smooth muscle [5,8].…”
Section: Introductionmentioning
confidence: 99%